2016
DOI: 10.1155/2016/2180946
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis ofXeroderma PigmentosumGroups A and C by Detection of Two Prevalent Mutations in West Algerian Population: A Rapid Genotyping Tool for the FrequentXPCMutation c.1643_1644delTG

Abstract: Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder. Considering that XP patients have a defect of the nucleotide excision repair (NER) pathway which enables them to repair DNA damage caused by UV light, they have an increased risk of developing skin and eyes cancers. In the present study, we investigated the involvement of the prevalent XPA and XPC genes mutations—nonsense mutation (c.682C>T, p.Arg228X) and a two-base-pair (2 bp) deletion (c.1643_1644delTG or p.Val548Ala fsX25), respectively—in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
2
9
0
5
Order By: Relevance
“…Soufir et al [ 33 ] estimated the common ancestry to have occurred 1250–1500 years ago; this dates with the Saracens’ i.e., Arab-Muslims’ conquest of South Europe. Given reports of the same mutation in patients from Italian, Spanish, Egyptian, Algerian, and Libyan ancestries, c.1643_1644delTG was suggested to be a founder mutation for the Mediterranean region [ 43 , 46 ]. Nonetheless, c.1643_1644delTG mutation was also reported in Sudanese and German patients of Arabian ancestries.…”
Section: Discussionmentioning
confidence: 99%
“…Soufir et al [ 33 ] estimated the common ancestry to have occurred 1250–1500 years ago; this dates with the Saracens’ i.e., Arab-Muslims’ conquest of South Europe. Given reports of the same mutation in patients from Italian, Spanish, Egyptian, Algerian, and Libyan ancestries, c.1643_1644delTG was suggested to be a founder mutation for the Mediterranean region [ 43 , 46 ]. Nonetheless, c.1643_1644delTG mutation was also reported in Sudanese and German patients of Arabian ancestries.…”
Section: Discussionmentioning
confidence: 99%
“…Both GG-NER and TC-NER involve the basic mechanism: (1) recognition of the damaged sites (in transcribed and non-transcribed regions of the genome, respectively); (2) verification of DNA damage; (3) excision of damaged oligomers; and (4) gap filling by ligating intact molecules [ 90 ]. Defects in the NER pathway causes rare autosomal recessive diseases such as Xeroderma pigmentosum (XP), Cockayne syndrome (CS), and trichothiodystrophy (TTD) [ 98 , 99 , 100 ]. NO was shown to inhibit DNA-adduct NER in human fibroblasts, including UVC and cisplatin derived DNA adducts [ 101 ].…”
Section: Role Of No In Cancer Biologymentioning
confidence: 99%
“…Since, we started studying XP we reported five complementation groups (XP-A, C, D, E, and V) in Tunisia. The mutations with founder effect responsible for the XP-C (Ben Rekaya et al, 2009) and XP-A phenotypes (Messaoud et al, 2010) have been also found in other North African countries (Soufir et al, 2010) such as Morocco (Senhaji et al, 2013; Kindil et al, 2017), Egypt (Amr et al, 2014), Algeria (Bensenouci et al, 2016), and Libya (unpublished data). The XP-D and XP-E forms have been recently identified thanks to whole exome sequencing (WES) technology (Ben Rekaya et al, 2018).…”
Section: Introductionmentioning
confidence: 76%